Inflammatory burden as a prognostic biomarker for cancer. Issue 6 (June 2022) - Xie, Hailun; Ruan, Guotian; Ge, Yizhong; Zhang, Qi; Zhang, Heyang; Lin, Shiqi; Song, Mengmeng; Zhang, Xi; Liu, Xiaoyue; Li, Xiangrui; Zhang, Kangping; Yang, Ming; et al.
Summary: Background and aims: Systemic inflammation is the most representative host–tumor interaction in cancer. This study aimed to develop a novel inflammatory burden index (IBI) to assess the inflammatory burden of different cancers and predict the prognosis of patients with cancer. Methods: A total of 6359 cancer patients admitted to multiple centers from 2012 through 2019 were included in this study. The IBI was formulated as C-reaction protein × neutrophil/lymphocyte. Survival differences between the groups were compared using the Kaplan–Meier method. Cox proportional hazard regression analysis was used to estimate the hazard ratio (HR) and 95% confidence interval (CI). Logistic regression analysis was used to assess the association between the inflammatory burden index and outcomes. Results: Cancers assessed by the IBI could be classified as high, moderate, or low inflammatory burden and had different prognostic stratification effects (46.5% vs 61.0% vs 83.0%; P < .001). Compared with other systemic inflammation biomarkers, the IBI had the highest accuracy in predicting survival. Patients with a high IBI had significantly lower survival rates than those with a low IBI (45.7% vs 69.1%; P < .001). For every standard deviation increase in the IBI, the risk of poor prognosis for patients with cancer increased by 10.3% (HR, 1.103; 95% CI, 1.072–1.136; P < .001). The IBI could be used as a useful prognostic supplement in the pathological stage. A high IBI was an independent high-risk factor that affected patient's physical condition, malnutrition, cachexia, and short-term outcomes and an independent risk factor for patients with cancer in both validation cohorts a (hazard ratio, 1.114; 95% confidence interval, 1.072–1.157; P < .001) and b (hazard ratio, 1.125; 95% confidence interval, 1.060–1.193; P < .001). Conclusions: The IBI, as a novel indicator of systemic inflammation, is a feasible and promising predictive biomarker in patients with cancer and can be used to assess the inflammatory burden of different cancers.